2016
DOI: 10.1016/j.jash.2016.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D predicts the onset of orthostatic hypotension in older adults

Abstract: A number of small cross sectional studies have demonstrated that hypovitaminosis D (represented by low 25 hydroxyvitamin D (25OHD) levels) is associated with orthostatic hypotension (OH). We investigated if hypovitaminosis D is associated with the onset of OH in older adults over a followup of 4.4 years. 25OHD was categorized using sex specific quartiles; OH was defined as a drop of ≤20 mm Hg in systolic or ≤10 mm Hg in diastolic blood pressure <3 minutes of standing. Among 1,308 elderly without OH at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The results showed no significant differences between the two groups. A decrease in BMI [28] and autonomic dysfunction caused by low levels of 25(OH)D3 [29] may also contribute to the occurrence of OH. However, these indicators did not show any statistically significant differences between the two groups in this study and, therefore, are not considered to be the main influencing factors for OH.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed no significant differences between the two groups. A decrease in BMI [28] and autonomic dysfunction caused by low levels of 25(OH)D3 [29] may also contribute to the occurrence of OH. However, these indicators did not show any statistically significant differences between the two groups in this study and, therefore, are not considered to be the main influencing factors for OH.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that, in patients with vitamin D deficiency, regardless of the neurologic level, the verticalization time with the tilt table is longer than in those with non-deficient vitamin D levels. In the literature, there are some studies conducted on older people [17,18], oldest-old people [13], and patients with Parkinson's disease [14], all of which suggest that low vitamin D status is associated with orthostatic hypotension. In a systematic review and meta-analysis about hypovitaminosis D and orthostatic hypotension, it was concluded that hypovitaminosis D was associated with orthostatic hypotension, independent of potential confounders [16].…”
Section: Discussionmentioning
confidence: 99%
“…Orthostatic hypotension is defined as a decrease in systolic blood pressure of at least 20 mm Hg, or a reduction in diastolic blood pressure of at least 10 mm Hg, upon a change in body position from a supine position to an upright posture, regardless of the presence of symptoms [12]. There are studies showing the relationship between orthostatic hypotension and vitamin D in some other diseases and in some geriatric groups [13][14][15][16][17][18]. Orthostatic hypotension seen in patients with spinal cord injury is the most important factor that negatively affects mobilization of patients.…”
Section: Introductionmentioning
confidence: 99%